Moral Disengagement and Generalized Social Trust as Mediators and Moderators of Rule-Respecting Behaviors During the COVID-19 Outbreak - Alessandri, Guido; Filosa, Lorenzo; Tisak, Marie S.; Crocetti, Elisabetta; Crea, Giuseppe; Avanzi, Lorenzo (Frontiers in Psychology, 2020)
In this study, we tested a theoretical model with moral disengagement and generalized social trust (GST) as mediators and moderators of the relationship between personality traits and rule respecting behaviors, (i.e., social distancing and stay-at-home), during the COVID-19 outbreak in Italy. The data were collected on 1,520 participants (61% males). Results showed that moral disengagement mediated the relationship between personality traits (emotional stability, narcissism, and psychopathy) and respect of social distancing. These indirect relationships were further moderated by GST. Among components of GST, trust in Government mediated the relationship between psychopathy and social distancing; trust in known others mediated the relationship between emotional stability, agreeableness and Machiavellianism with total number of exits; trust in unknown others mediated the relationship of emotional stability, agreeableness, conscientiousness, and psychopathy with average daily number of exits. The theoretical and practical importance of these results were discussed.